Substituent effects in carbon-nanotube-supported diiron monophosphine complexes for hydrogen evolution reaction. (1st December 2022) - Jin, Bo; Tan, Xiao; Zhang, Xuan-Xuan; Wang, Zi-Yi; Qu, Yong-Ping; He, Yan-Bin; Hu, Tuo-Ping; Zhao, Pei-Hua
Highlights: New diiron monophosphine precursors FeP R ( R = F, H, and Me) were prepared and characterized. A new family of CNT-supported diiron monophosphine hybrids CNT- f -FeP R was fabricated and characterized. Substituent effects of FeP R on electrocatalytic HER behaviros of CNT- f -FeP R were investigated systematically. Electrochemical studies indicate hybrid CNT- f -FeP F exhibits a better HER activity in 0.1 M H2 SO4 . DFT calculation reveals hybrid CNT- f -FeP F has a lower Δ G H* value relative to homologues CNT- f -FeP R ( R = H, Me). Abstract: In order to explore substituent effects of PR3 -phosphine ligands of diiron dithiolato complexes on the catalytic performances of [FeFe]-hydrogenase mimics for hydrogen evolution reaction (HER) in an aqueous medium, three new diiron monophosphine complexes [( μ -SCH2 )2 N(C6 H4 CH2 CH2 OH)Fe2 (CO)5 P(C6 H4 R- 4 )3 ] (labeled as FeP R ; R = F, H, and Me) were prepared and can be further linked covalently into carbon nanotube (CNT) to construct the target CNT-supported hybrids denoting as CNT- f -FeP R . The molecular structures of diiron complexes FeP R are well characterized through element analysis, fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR) and X-ray crystallography, whereas the formations of target hybrids CNT- f -FeP R have been confirmed by using X-ray photoelectron spectroscopy (XPS), Raman and FT-IR. Notably, the electrochemical HER performances of target hybrids CNT- f -FeP R ( R = F, H, and Me) are studied and compared in 0.1 M H2 SO4 aqueous solution by means of linear sweep voltammetry (LSV), cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and density functional theory (DFT) calculation. Among these hybrids, the CNT- f -FeP F hybrid exhibits a more efficient HER activity in an aqueous media based on their electrochemical observations that the CNT- f -FeP F hybrid with F-substituted phosphine has lower applied overpotential, smaller Tafel slope, larger electrochemical active surface area, smaller charge transfer resistance, and lower hydrogen chemisorption free energy relative to its analogues CNT- f -FeP H and CNT- f -FeP Me with H- or Me-substituted phosphines. Graphical abstract: A new family of CNT-supported diiron monophosphine complexes denoting as CNT- f -FeP R ( R = F vs. H vs. Me) was constructed in order to investigate the substituent effects of diiron phosphine clusters FeP R on the electrochemical HER performances of hydrogenase-inspired catalysts CNT- f -FeP R in aqueous medium. Image, graphical abstract